UNESCO ROLE IN ADULT EDUCATION POLICY DEVELOPMENT AT THE END OF THE XX CENTURY - THE BEGINNING OF THE XXI CENTURY - Наталія Авшенюк (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2020)
The article is based on an integrated analysis of key UNESCO documents (Recommendations of the International Conference on Adult Education CONFINTEA (1985, 1997, 2003, 2009), Global Reports on Adult Learning and Education (2009, 2013, 2016, 2019) that outlines the impact of evidence-based research on educational policy in supporting the development of educational policy in adult learning in the global ed-ucational environment at the end of the XX and at the beginning of the XXI century. It is found that the development of adult education is necessary due to the dynamics of social, scientific and technological improvement; changes in the content and nature of work and social activities of people; increased free time and opportunities for its effective use; labor market demands, the main requirements of which are to increase the competence and skills of the professional. Adult involvement in lifelong learning not only encourages meeting own needs, but also ensures self-fulfillment to a free choice of a place, time and a pathway of improvement. It is proved that since the 1970s up to now UNESCO has played a key role in shaping and disseminating the concept of lifelong learning in education policy. The concept, in essence, involves the restructuring of the existing education system and use of educational perspectives of adults externally the traditional education system in order to influence the development of different social groups and individual development of each person. The world has accumulated considerable meaningful experience in the development of the theory and practice of adult education, which is accumulated, disseminated and implemented through the activities of international organizations on a global scale, including UNESCO. This international organization generates ideas and builds educational policies that are based on reliable statistics and the results of global empirical research.